The relationship between athletes' coping strategies and indicators of dominant states - Namazov A.K. ,; Olennikova M.V. ,; Vasilyeva V.S. ,; Grigoryev I.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of coping strategies for coping with stress among martial arts athletes with different experiences of successful competitive activities. Methods and structure of the study. The experimental base of the study consisted of martial arts athletes specializing in martial arts of the Institute of Physical Culture and Sports of Peter the Great St. Petersburg University. A total of 60 athletes took part, aged 18-24 years. Of these, 30 were successful (15 boys and 15 girls) and 30 were unsuccessful (15 boys and 15 girls). To identify coping strategies, the Youth Coping Scale methodology was used, authored by Erica Frydenberg and Ramon Lewis, adapted by T.L. Kryukova. Results and conclusions. In a situation of coping with stress, successful athletes actively use all types of coping strategies, choosing them depending on the characteristics of the situation, which allows them to cope with stress most effectively at the moment. Unsuccessful athletes have a much smaller set of coping strategies. In a stressful situation, such athletes try to cope with stress, first of all, by continuing to work hard in training.